An Insight into the Role of Reactant Structure Effect in Pd/C Catalysed Aldehyde Hydrogenation - Marta Stucchi; Francesca Vasile; Stefano Cattaneo; Alberto Villa; Alessandro Chieregato; Bart D. Vandegehuchte; Laura Prati (Nanomaterials, 2022)
The different activity of a 1% Pd/carbon catalyst towards aromatic and aliphatic aldehydes hydrogenation has been explored by 13C NMR relaxation. The ratio between T1 relaxation times of adsorbed (ads) and free diffusing (bulk) molecules (T1ads/T1bulk) can be used as an indicator of the relative strength of interaction between the reactant and the catalytic surface, where the lower the T1ads/T1bulk, the higher the adsorption strength. It can be seen that 1% Pd/carbon showed a reverse catalytic behaviour towards benzaldehyde and octanal hydrogenation, which can be explained by analysing the T1 relaxation times related to each substrate in the presence of the catalyst. Comparing and correlating the different T1ads/T1bulk values, we were able to prove that the different catalytic results mainly depend on the contrasting adsorption behaviour of substrates on the catalyst. Moreover, the role of the solvent has been disclosed, as NMR results revealed that the adsorption of the reactants was strongly affected by the choice of solvent, which is revealed to be critical in modulating catalytic activity. As a consequence, T1ads/T1bulk measurements can provide a guide to the selection of appropriate reaction conditions for improving catalytic activity.